(untitled) (Journal of Pharmaceutical Negative Results, 2023)
Background The thought of experience of surgery with anaesthesia promotesintense anxiety. Thisstresscan give rise todetrimental events like perioperative cardiac problems, increased anaesthesia requirements, intense postoperative pain and increased length of hospital stay.Many factors impact the anxiety statusat the time of surgery. This study was designed to evaluate the prevalence of anxiety in adultsscheduled for elective surgery in a tertiary care hospital. Methods 428 patients scheduled for differentelective surgeries were asked 6 questions based on the Amsterdam preoperative anxiety score to determine their anxiety status. The factorsevaluated were age, sex, socioeconomic status, type of surgery and history of prior surgery. The patients were asked questions regarding problems in surgery, recovery from anaesthesia, needle pricks,etc as these can cause anxiety. Results The incidencerate of anxiety was 89.71%. The mild anxiety prevalence in male patients and female patients were 170 (44.27%) and 214 (55.73%%)with a p value of <0.005. Patients with nil anxiety were 44 (10.28%), mild anxiety were 207 (48.36%), moderate anxiety were 121 (28.27), severe anxiety were 56 (13.08%). Conclusion Preoperative anxiety has a significantimpact on the surgery outcomes. It could cause increase heart rate, and thus, might accelerate bleeding. Besides, it has been shown that increased level of preoperative anxiety may lead to increased postoperative pain-relieving drug requirement. Hence on assessment of the presence of anxiety and the level, adequate anxiolytic premedication can be prescribed. In addition, the relationship between anxiety and age, gender, type of surgery, education and socioeconomic status can be evaluated, as these may have an influence on the anxiety levels and severity. The overall prevalence of anxiety in this part of the country was found to be higher. The prevalence was increased in females.